Efeito de diferentes sistemas de acabamento e polimento na rugosidade superficial de resina composta - Dietrich, Claudia Helena (2014)
Given the routine use of polishing and finishing systems in Restorative Dentistry, the search for better outcomes of these materials, it is essential to optimize the results. Thus, this study aimed to evaluate in vitro the effect of polishing finishing and polishing systems on surface roughness of composite resin. Specimens were made for each group (n = 10), totaling 80 specimens. Randomly distributed among the eight selected polishing systems. The polishing systems were employed after the stabilize the polishing and metallographic specimens was followed according to the manufacturer's instructions. The specimens were stored for 24 hours in aqueous solution (room temperature) underwent evaluation of roughness on rugosimeter, and surface roughness as groups were compared using ANOVA, followed by post-hoc Tukey test at a significance level 5%, with p = 0.05. Was no statistical difference between finishing and polishing systems evaluated. The finishing and polishing systems produce different patterns on the surface roughness of the composite, and the rotating disc systems based on superior results obtained with smaller surface roughness measurements.